Efektivitas Metode Keteladanan Dalam Meningkatkan Kualitas Akhlak di2 Madrasah Tsanawiyah As’adiyah Putri I Pusat Sengkang - Nurfadhillah, Nurfadhillah (JURNAL AL-QAYYIMAH, 2018)
This paper examines the effectiveness of the method of example in improving the quality of morals in Mts's daughter I the Centre of Sengkang. This type of research is a field research. The results showed that the application of the method of example in Mts As'adiyah Princess 1 Sengkang Center is constantly working to improve the quality of education in morals, in order to be able to answer the challenges of the times in the life of religion, nation and a country. The impact of the application of the method of example against the morals of students namely morals learners already increased from year to year in which the application of religious values have become routine and the motivation of the teachers, so that learners have already used to it.